Comprehensive geriatric assessment in the emergency department - Ellis G (Dove Medical Press, 2014)
Graham Ellis,1 Trudi Marshall,2 Claire Ritchie2 1Medicine for the Elderly, Monklands Hospital, Airdrie, Scotland, UK; 2Kirklands Hospital, Bothwell, Scotland, UK Abstract: Changing global demography is resulting in older people presenting to emergency departments (EDs) in greater numbers than ever before. They present with greater urgency and are more likely to be admitted to hospital or re-attend and utilize greater resources. They experience longer waits for care and are less likely to be satisfied with their experiences. Not only that, but older people suffer poorer health outcomes after ED attendance, with higher mortality rates and greater dependence in activities of daily living or rates of admission to nursing homes. Older people’s assessment and management in the ED can be complex, time consuming, and require specialist skills. The interplay of multiple comorbidities and functional decline result in the complex state of frailty that can predispose to poor health outcomes and greater care needs. Older people with frailty may present to services in an atypical fashion requiring detailed, multidimensional, and increasingly multidisciplinary care to provide the correct diagnosis and management as well as appropriate placement for ongoing care or admission avoidance. Specific challenges such as delirium, functional decline, or carer strain need to be screened for and managed appropriately. Identifying patients with specific frailty syndromes can be critical to identifying those at highest risk of poor outcomes and most likely to benefit from further specialist interventions. Models of care are evolving that aim to deliver multidimensional assessment and management by multidisciplinary specialist care teams (comprehensive geriatric assessment). Increasingly, these models are demonstrating improved outcomes, including admission avoidance or reduced death and dependence. Delivering this in the ED is an evolving area of practice that adapts the principles of geriatric medicine for the urgent-care environment. Keywords: ED, frailty, models of care